2016
DOI: 10.11646/zootaxa.4144.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Paracercion ambiguum sp. nov. from Lang Son, Vietnam (Zygoptera: Coenagrionidae)

Abstract: One new species of Paracercion Weekers and Dumont, 2004 (Paracercion ambiguum Kompier & Yu, 2016, holotype male, Vietnam, Lang Son province, Huu Lien Nature Reserve, 1-XII-2013, deposited in Institute of Entomology, College of Life Sciences of Nankai University, Tianjin, China) is proposed on the basis of molecular and morphological evidence. A COI gene tree is presented for Paracercion species and several morphologically related genera. The species is described and illustrated for both sexes. Diagnostic figur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 699 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Therefore, these three species may have originated from one widely distributed ancestral species. Dumont (2004) and Ning et al (2016) also suggested that P. sieboldii shared a common ancestor with the continental P. v-nigrum .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, these three species may have originated from one widely distributed ancestral species. Dumont (2004) and Ning et al (2016) also suggested that P. sieboldii shared a common ancestor with the continental P. v-nigrum .…”
Section: Discussionmentioning
confidence: 99%
“…Specimens were examined and dissected under a Zeiss V8 stereomicroscope. More than 600 specimens (including dried specimens) were identified by Xin Yu and Xin Ning in terms of the corresponding literatures ( Dumont, 2004 ; Yu, 2008 ; Yu & Bu, 2011 ; Ning et al, 2016 ). All the specimens were stored at the College of Life Sciences, Chongqing Normal University.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…COI sequences greater than 500-bp, considered as standard barcode according to the Barcode of Life Data System (BOLD) 27 . In present study, 657-bp length of COI gene fragment of Ischnura aurora is used, as same base pair length has been analysed for the same species by Dijkstra et al 5 ; Ning et al 24 ; Ramage et al 26 , while only 451-bp length has been used by Futahashi 12 .…”
Section: Length Of Coi Gene Barcodementioning
confidence: 99%
“…COI gene based DNA barcoding and phylogenetic relationships of approximately 211 species of family Coenagrionidae have been done worldwide 1,2,3,5,9,13,17,20,24,25,29,33,34 .…”
Section: Introductionmentioning
confidence: 99%